Green Accounting, Debt Default, and Market Capitalization: Multiple Linear Regression on Stock Prices - Thomas Averio (Journal of Business and Economics Research (JBE), 2026)
This study purports to examine whether green accounting, debt default, and market capitalization affect stock prices in emerging markets, with a particular focus on Indonesia. The research uses consumer non-cyclicals sector companies in Indonesia as the sample. The observation period covers 2020 to 2024. The study implements multiple linear regression to analyze the data. The findings indicate that green accounting, debt default, and market capitalization each exert a significant and positive influence on stock prices, with a significance level of 0.000 for all independent variables. Furthermore, the coefficient of determination indicates that green accounting, debt default, and market capitalization explain 15.4% of the variation in stock prices. These results reinforce previous empirical studies and further confirm that investors strongly consider green accounting practices, debt levels, and market capitalization when making investment decisions.